Partial Replacement of Fish Meal With Shrimp Waste Meal: Effects on Growth, Digestibility, and Immunity in Juvenile Beluga Sturgeon ( Huso huso ) - Taheri, Amirsoheil; Abedian Kenari, Abdolmohammad; Aftabgard, Maryam (Aquaculture research, 2025)
This study aimed to investigate the effects of replacing different levels of dietary shrimp waste meal (SWM) with fish meal (FM) on growth performance (GP), carcass composition (CC), apparent digestibility (AD), and innate immunity of juvenile beluga sturgeon ( Huso huso ). A total of 180 juvenile beluga with an average weight of 130.0 ± 6.5 g were assigned to five treatments (with three replicates each): SWM0 (control group), SWM5, SWM10, SWM15, and SWM20, corresponding to 0%, 5%, 10%, 15%, and 20% inclusion of SWM in place of FM in their diets for 8 weeks. The results showed that GP and protein AD declined in the SWM5 group ( p < 0.05), while no significant differences were observed in GP and AD across the other treatments compared to the control ( p > 0.05). Regarding CC, no significant differences were found among the treatments. The fatty acid (FA) profile of the muscles in juvenile beluga fed with SWM5–20 was similar to that of the control group, with the only notable difference being a decrease in eicosapentaenoic acid (EPA) as dietary SWM levels increased ( p < 0.05). The essential amino acid (EAA) content also decreased in the SWM20 group ( p < 0.05), although the EAA‐to‐nonessential amino acid (NEAA) ratio in the SWM5–20 treatments was not significantly different from that of the control group ( p > 0.05). The highest levels of serum lysozyme (LYZ) and alternative complement hemolytic (ACH50) activity were observed in the SWM15 group, with the lowest levels found in the control group ( p < 0.05). The results showed that substituting FM with SWM at a rate of 15%–20% in the diet had no significant and negative impact on GP, nutritional value, or digestibility. On the contrary, it boosted the immune system of juvenile beluga sturgeon ( H. huso ). The positive immunostimulation appears to be related to the beneficial effects of amino acid (AA) or imino acids (IAs) and chitin as well as their recognition by mannose/fucose receptors attached to white blood cells.